Existence and Uniqueness Results of Positive Solution of a Class of Singular Duffing Oscillators - Nadir Benkaci-Ali (IndoMS, 2022)
In this paper, we give existence and uniqueness results of nontrivial positive solution of the singular and non-autonomous kind of Duffing oscillator by using fixed point index theory.